039 Rates of lymphopenia in years 1–4 in patients with relapsing multiple sclerosis treated annually with cladribine tablets. Issue 6 (24th May 2018) - Cook, Stuart; Comi, Giancarlo; Giovannoni, Gavin; Rieckmann, Peter; Sorensen, Per Soelberg; Vermersch, Patrick; Dangond, Fernando; King, John; Hicking, Christine
Abstract : Introduction: The CLARITY and CLARITY Extension studies demonstrated the efficacy of cladribine tablets in patients with relapsing multiple sclerosis. The most common adverse event was lymphopenia, consistent with the mechanism of action of cladribine tablets. Objective was to evaluate whether lymphopenia persists following annual treatment with cladribine tablets. Methods: Lymphopenia by grade (NCI CTCAE v3.0) for patients randomised to cladribine tablets 3.5 mg/kg in CLARITY and re-randomised to cladribine tablets 3.5 mg/kg in CLARITY Extension (7 mg/kg cumulative dose over 4 years; n=186) are reported. Patients with Grade 0 lymphopenia (≥1.0×10 9 cells/L) before the first course of cladribine tablets and Grade 0/1 (≥0.8×10 9 cells/L) prior to administration in Years 2, 3 and 4 were included in the analysis. Results: 176 patients were Grade 0 at CLARITY baseline and 167 were Grade 0/1 at CLARITY Extension baseline. Grade 3 lymphopenia was observed in 1% of patients at Week 13 in Year 1, and in 7%, 11% and 12% at Week 12 in Years 2, 3 and 4, respectively. By Week 24 in Years 1, 2, 3 and 4, Grade 3 lymphopenia was observed in 1%, 4%, 4% and 4% of patients, respectively. By Week 36 in Years 1, 2, 3 and 4, Grade 3 lymphopenia was observed in 1%, 2%, 2% and 2% of patients, respectively. Grade 3 lymphopenia was only observed in Week 48 of Year 2 (1% of patients). Grade 3 lymphopenia was reported in <18% of patients at any time point. No patients had Grade 4 lymphopenia at the end of any years. Conclusion: No patients included in this analysis experienced Grade 4 lymphopenia at the end of any treatment year. Grade 3 lymphopenia was uncommon. This study demonstrates the effectiveness of lymphocyte-based treatment criteria in minimising the incidence of severe, sustained lymphopenia during treatment with cladribine tablets.